Financial Toxicity in the Clinical Encounter: A Paired Survey of Patient and Clinician Perceptions - Andrea Garcia-Bautista, MD; Celia Kamath, PhD; Nicolas Ayala, MBBS; Emma Behnken, BA; Rachel E. Giblon, MS; Derek Gravholt, MS; María José Hernández-Leal, PhD; Jessica Hidalgo, MD; Montserrat Leon Garcia, PharmD, MPH; Elizabeth H. Golembiewski, MPH, PhD; Andrea Maraboto, MD; Angela Sivly, CCRP; et al. (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2023)
Objective: To compare the agreement between patient and clinician perceptions of care-related financial issues. Patients and Methods: We surveyed patient-clinician dyads immediately after an outpatient medical encounter between September 2019 and May 2021. They were asked to separately rate (1-10) patient’s level of difficulty in paying medical bills and the importance of discussing cost issues with that patient during clinical encounters. We calculated agreement between patient-clinician ratings using the intraclass correlation coefficient and used random effects regression models to identify patient predictors of paired score differences in difficulty and importance of ratings. Results: 58 pairs of patients (n=58) and clinicians (n=40) completed the survey. Patient-clinician agreement was poor for both measures, but higher for difficulty in paying medical bills (intraclass correlation coefficient=0.375; 95% CI, 0.13-0.57) than for the importance of discussing cost (−0.051; 95% CI, −0.31 to 0.21). Agreement on difficulty in paying medical bills was not lower in encounters with conversations about the cost of care. In adjusted models, poor patient-clinician agreement on difficulty in paying medical bills was associated with lower patient socioeconomic status and education level, whereas poor agreement on patient-perceived importance of discussing cost was significant for patients who were White, married, reported 1 or more long-term conditions, and had higher education and income levels. Conclusion: Even in encounters where cost conversations occurred, there was poor patient-clinician agreement on ratings of the patient’s difficulty in paying medical bills and perceived importance of discussing cost issues. Clinicians need more training and support in detecting the level of financial burden and tailoring cost conversations to the needs of individual patients.